Sosialisasi Pelaporan Keuangan Pelaku UMKM Syariah Di Kecamatan Namang Kabupaten Bangka Tengah - ulyah, Himmatul Ulyah (Universitas Bangka Belitung, 2024)
This community service aims to provide socialization and simulations related to MSME accounting guidelines so that MSMEs can prepare and report their finances in accordance with applicable financial standards. The participants of this community service are MSME in Namang District, Central Bangka Regency, Bangka Belitung Islands Province. This method of community service is socialization and material assistance as well as a simulation of the implementation of MSME accounting guidelines. The speaker at this event was a lecturer at IAIN SAS Bangka Belitung. The result of this community service is that participants gain knowledge and knowledge about MSME accounting and participants can apply MSME accounting for their business